PENGARUH MODAL INTELEKTUAL TERHADAP KINERJA BISNIS PADA UKM DI KABUPATEN SIDOARJO (STUDI EMPIRIS PADA UKM DI BIDANG INDUSTRI) - Sari, Nurul Puspita (Jurnal Akuntansi AKUNESA, 2020)
This study aims to determine the effect of intellectual capital on business performance in small and medium business (SMEs) in Sidoarjo. The population used is SMEs in the Sidoarjo. Based on quantitative research methods with a purposive sampling technique and data collection through questionnaires, there are 138 SMEs who become research samples with criteria in the field of small and medium industries. The data analysis method used is the WarpPLS 3.0 program. The result showed that human capital, customer capital, and structural capital significantly influence the performance of SMEs businesses.